2021
DOI: 10.15252/embr.202051806
|View full text |Cite
|
Sign up to set email alerts
|

ATF3 induces RAB7 to govern autodegradation in paligenosis, a conserved cell plasticity program

Abstract: Differentiated cells across multiple species and organs can re‐enter the cell cycle to aid in injury‐induced tissue regeneration by a cellular program called paligenosis. Here, we show that activating transcription factor 3 (ATF3) is induced early during paligenosis in multiple cellular contexts, transcriptionally activating the lysosomal trafficking gene Rab7b. ATF3 and RAB7B are upregulated in gastric and pancreatic digestive‐enzyme‐secreting cells at the onset of paligenosis Stage 1, when cells massively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 113 publications
(184 reference statements)
2
27
0
Order By: Relevance
“…Recently a conserved program for cellular plasticity in epithelial cells was defined, termed paligenosis. Paligenosis occurs via 3 stages: Stage1, massive activation of autophagy and lysosomal activity as mTORC1 is extinguished; Stage2, re-expression of progenitor or embryonic markers without mTORC1 expression; Stage3, induction of high mTORC1 with cell cycle entry 19 , 20 , 74 77 , consistent with a previous study 78 . Previously, paligenosis has been shown as the process differentiated cells use to return to the progenitor state in precancerous states like gastric metaplasia.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Recently a conserved program for cellular plasticity in epithelial cells was defined, termed paligenosis. Paligenosis occurs via 3 stages: Stage1, massive activation of autophagy and lysosomal activity as mTORC1 is extinguished; Stage2, re-expression of progenitor or embryonic markers without mTORC1 expression; Stage3, induction of high mTORC1 with cell cycle entry 19 , 20 , 74 77 , consistent with a previous study 78 . Previously, paligenosis has been shown as the process differentiated cells use to return to the progenitor state in precancerous states like gastric metaplasia.…”
Section: Resultssupporting
confidence: 87%
“…6a ). The C3-tumor cluster had high mTORC1 activity ( MLST8, RPS6 ) and high proliferation ( MKI67, MCM2 ), characteristics of late paligenosis when cells re-enter the cell cycle (stage 3) 74 , 76 , 77 (Fig. 6b and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…45,73 The first stage depends on the early-response transcription factor ATF3, which in turn up-regulates expression of the lysosome and autophagy trafficking protein RAB7B. 75 The next stage involves the induction of the pathognomonic TFF2 as a component of MUC6-containing mucous granules. Even before autodegradative pathways are activated, one of the earliest events is that chief cells en route to SPEM decrease expression of Mist1.…”
Section: The Origin Of Spasmolytic Polypeptide-expressing Metaplasia ...mentioning
confidence: 99%
“…68 Moreover, as mentioned above, apoptosis of a small cohort of cells has been noted after SPEM induction, with many more dying if the process is disrupted by drugs or mutations that affect completion of paligenosis. 40,45,68,73,75 Some differences in results may be due to differences in the various fluorescent LSL-Rosa26R reporter strains. We have observed that Confetti mouse labeling of chief cells is lost after induction of acute parietal cell loss, while mapping with mTmG or YFP strains is not (data not shown).…”
Section: The Origin Of Spasmolytic Polypeptide-expressing Metaplasia ...mentioning
confidence: 99%
“…GO analysis also showed that the differential genes were mainly related to cell proliferation, AP-1 complex and transforming factor complex. In addition to this, the 10 genes with the most significant differences have been previously reported to be related to apoptosis, cell proliferation, vascular remodeling, inflammation and immunity, damage repair, fibrosis, cell migration, and differentiation ( Gay et al, 2011 ; Palumbo-Zerr et al, 2015 ; Cook et al, 2020 ; Cao et al, 2021 ; Ding et al, 2021 ; Liu et al, 2021 ; Olaloye et al, 2021 ; Radyk et al, 2021 ; Tang et al, 2021 ). These results were consistent with the findings of the previous studies conducted, which explored the occurrence and development mechanism of IUAs.…”
Section: Discussionmentioning
confidence: 93%